Virtual reality and gamification in hospitality education at front desk - Ismail, Nurul Halimatul Asmak; Awwad, Samer A.B.; Thinakaran, Rajermani; Quah, Wei Boon; Muniandy, Mohana (Association for Information Communication Technology Education and Science, 2024)
Virtual reality (VR) is recognized as an intelligent and digital technology that has impacted numerous sectors and environments. VR in the classroom acts like a digital tool for the students and the teachers to achieve educational goals as it enhances understanding, critical thinking, visualization levels, and problem-solving skills. In addition, gamification as a motivational factor is integrated with VR. This study investigates the usage of VR and gamification in hospitality educational environment mainly at the front desk. This is to be beneficial to an individual’s knowledge and abilities, which should be prioritized in the future, and that earlier experience should be given credit for future employability and education quality.